2012
DOI: 10.1140/epjb/e2012-30317-6
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic response of a model silica glass under shear and pressure

Abstract: The Mechanical Response of a Model Silica Glass is studied extensively at the submicrometer scale, with the help of atomistic simulations. The analysis of the response to a hydrostatic compression is compared to recent experimental results. The irreversible behaviour and the variation of intertetrahedral angles is recovered. It is shown that the atomistic response is homogeneous upon compression, in opposition with the localization along shear bands occuring during shear deformation with constant volume. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 82 publications
(110 reference statements)
16
79
0
Order By: Relevance
“…The very high quenching rate (>10 11 K s À1 ) used in atomistic simulations is far larger than the largest experimental quenching rate ($10 6 K s À1 ). However, the numerically obtained equilibrium structure is very close to the experimental one 4 at least for smallscale order as measured by the pair correlation function, suggesting that the classic empirical interatomic interactions used for the calculation implicitly accelerate the relaxational dynamics. 25 This is why a comparison between classic molecular dynamics and experimental measurements is not hopeless and can be used to emphasize the role of the local structure on the mechanical properties.…”
Section: Elasticity Versus Plasticity In Amorphous Materialssupporting
confidence: 60%
See 2 more Smart Citations
“…The very high quenching rate (>10 11 K s À1 ) used in atomistic simulations is far larger than the largest experimental quenching rate ($10 6 K s À1 ). However, the numerically obtained equilibrium structure is very close to the experimental one 4 at least for smallscale order as measured by the pair correlation function, suggesting that the classic empirical interatomic interactions used for the calculation implicitly accelerate the relaxational dynamics. 25 This is why a comparison between classic molecular dynamics and experimental measurements is not hopeless and can be used to emphasize the role of the local structure on the mechanical properties.…”
Section: Elasticity Versus Plasticity In Amorphous Materialssupporting
confidence: 60%
“…In this article, we will take examples from different model amorphous materials obtained in this way and constructed with different empirical interatomic potentials: Lennard-Jones interactions as an example of two-body interactions, 23 StillingerWeber potentials with a set of variable parameters to tune the bond directionality (three-body interactions), 3 and BKS potential with effective Coulomb interactions and two different species that are used to model silica glasses. 4 The variety of these interactions will allow us to underline the role of composition on the elementary processes of the mechanical response.…”
Section: Elasticity Versus Plasticity In Amorphous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, in contrast to PID, we assume that shear plays a role in triggering the densification process, which is in agreement with recent molecular dynamics studies [22].…”
Section: Indentation Behaviour: Pressure and Shear -Induced Densificasupporting
confidence: 90%
“…Molecular dynamics (MD) has been extensively used to study silicate glasses [1][2][3] in areas of nanosecond aging of silica [4][5][6], pressure and shear response [7][8][9], and cooling-rate effects [10][11][12][13]. In this work, we use the BKS interatomic potential [14], which has been used frequently to study the glass properties of silica, and has been demonstrated to capture experimentally observed behavior.…”
Section: Introductionmentioning
confidence: 99%